Agnes Browne - Sheridan, Jim; Huston, Anjelica ([S.l.] : October Films [production company] ; Kuala Lumpur : Speedy Video [distributor])
Adapted from Brendan O' Carroll's best-selling Irish novel The Mammy, the film is set in Dublin in 1967
n.2 is acquisition for KPI (Kelab Pencinta Ilmu)
Executive producer, Morgan O' Sullivan, Tom Palmieri ; screenplay, John Goldsmith, Brendan O' Carroll
Starring: Angelica Huston, Marion O' Dwyer, Tom Jones
Keywords: Family in motion pictures; Family -- Drama -- Ireland